2020
DOI: 10.1080/15538362.2020.1768616
|View full text |Cite
|
Sign up to set email alerts
|

Low-Tunnel Strawberry Production: Comparison of Cultivars and Films

Abstract: Growing repeat-fruiting strawberries (Fragaria ×ananassa Duchesne ex Rozier) under low tunnels can extend a strawberry harvest season from a few weeks to several months. Yields from multiple dayneutral cultivars have been compared under a single film, and yields from single cultivars have been compared under multiple films, but a study of possible cultivar and film interaction effects in low tunnels has not been reported. From 2014-2018, six cultivars were compared under low tunnels covered with a standard pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…(2020) reported that 'Albion' performed best under KLP and under a relatively transparent film that had transmission properties similar to those of TRP. While there were no statistically significant differences in yield on white mulch among films in the present study, which aligns with other work (Willden et al, 2021), the average yields on white mulch were greatest under KLP, UVO, and TRP, indicating that our findings related to the best film for 'Albion' on white mulch are strikingly similar to those of Lewers et al (2020). Also on white mulch, Willden et al (2021) observed that yield tended to increase with the level of UV reduction.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…(2020) reported that 'Albion' performed best under KLP and under a relatively transparent film that had transmission properties similar to those of TRP. While there were no statistically significant differences in yield on white mulch among films in the present study, which aligns with other work (Willden et al, 2021), the average yields on white mulch were greatest under KLP, UVO, and TRP, indicating that our findings related to the best film for 'Albion' on white mulch are strikingly similar to those of Lewers et al (2020). Also on white mulch, Willden et al (2021) observed that yield tended to increase with the level of UV reduction.…”
Section: Discussionsupporting
confidence: 90%
“…However, when plants were grown on white mulch, yields were consistently highest under the UVreducing films KLP and UVO (the former also reduced NIR transmission). One-off exceptions to this trend were white mulch/ UVT, white mulch/TRP, and black mulch/ KLP, which each performed very well during one of two years [above average plant performance under KLP has also been reported by (Lewers et al 2020)]. This trend may suggest an interaction between the reflectance and absorption properties of the mulches and the transmission profiles of films.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations